2005
DOI: 10.1002/j.1551-8833.2005.tb10847.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stannous chloride and phosphate for lead corrosion control

Abstract: Because of health hazards associated with lead toxicity, the U.S. Environmental Protection Agency in 1991 promulgated the Lead and Copper Rule (LCR), which established an action level for lead at 15 μg/L as Pb. Even though lead pipes are no longer installed in U.S. distribution systems, many cities still have lead service connections that can release lead into the water. To help control lead concentrations, many water utilities add corrosion inhibitors to the treated water to create a protective scale layer on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…showed that phosphorus addition increased biofilm bacterial cell number, which agrees with other research work on the effects of phosphorus on biofilm growth in drinking water systems (Lehtola et al 2002;Chu et al 2005;Hozalski et al 2005). Besides the positive effects on the biofilm cell number, we also found that the addition of phosphorus could decrease the biofilm EPS production.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…showed that phosphorus addition increased biofilm bacterial cell number, which agrees with other research work on the effects of phosphorus on biofilm growth in drinking water systems (Lehtola et al 2002;Chu et al 2005;Hozalski et al 2005). Besides the positive effects on the biofilm cell number, we also found that the addition of phosphorus could decrease the biofilm EPS production.…”
Section: Discussionsupporting
confidence: 91%
“…Miettinen et al (1997) and Sathasivan & Ohgaki (1999) suggested keeping the phosphorus level as low as possible or not introducing phosphorus to DWDS at all in order to maintain the biological stability of drinking water. Dosages from 1 mg l 21 to 400 mg l 21 of phosphorus have been proved to increase microbial growth in water and biofilm in DWDS (Lehtola et al 2002;Chu et al 2005;Hozalski et al 2005). Besides the effects on microbial cell growth, there is evidence that the level of phosphorus could affect the EPS production (Hoa et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Utilities intending to control Pb release under the LCR may employ certain water treatment changes that induce the formation of less soluble compounds on the interior pipe wall. Aside from pH and/or alkalinity adjustment, among the most widely used approaches for corrosion control is orthophosphate addition, which has been shown to reduce Pb levels in comparison with systems without treatment (Cardew 2009, Hayes et al 2008, Hozalski et al 2005, Edwards & McNeill 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Once Sn is oxidized, it would be expected to remain in an oxidized state. Sn scaling of pipe walls, which was confirmed to occur through pipescale analysis (see Section 3.7), was expected because Sn is a corrosion inhibitor known to coat pipe walls (Hozalski et al, 2005(Hozalski et al, , 2010. As the full-scale demonstration spanned only 60 days, it is unknown if Sn concentrations at the end of the distribution system would remain constant if equilibrium was achieved after Sn further coated pipe walls.…”
Section: Sn and Cr Accumulationmentioning
confidence: 87%